Cryopreservation of seeds' threatened species - Bignoniaceae (Research, Society and Development, 2024)
Bignoniaceae family includes plant species that produce large amounts of seeds, stenospermic, thin, with two membranous wings, high lipid content and short lifespan under natural and artificial storage conditions, even though they are classified as orthodox seeds for the purposes of conservation. Such is the case of the Brazilian threatened native species Handroanthus impetiginosus, (Mart. ex DC.) Mattos, H. serratifolius (Vahl) S. Grose, Tabebuia aurea (Silva Manso) Benth. & Hook. f ex S. Moore and T. roseoalba (Ridl.) Sandwith, which have seeds with high lipid content named oleaginous or aleuro-oleaginous. Due to the characteristics of seed chemical components, storage behavior and vulnerability, an appropriate technique for conserving their genetic variability is a priority. Thus the objective of this study was to establish a cryopreservation technique for seeds of these species. In this study, the effect of exposure to liquid nitrogen at -196° C, on germinability of seeds, adopting rapid freezing (-263 °C.min.-1) and slow thawing (5 °C.min.-1), was tested for the seeds of these four species.  High germination percentages were obtained after exposure to liquid nitrogen, 89% for H. impetiginosus, 93% for H. serratifolius, 100% for T. aurea and 94% T. roseoalba. These results suggest that cryopreservation in liquid nitrogen is a safe approach and can be used to ensure long-term storage of these four plant species in cryogenic banks.